Desafios erosivos e o uso de dentifrício contendo SnCl2: implicações na resistência de união de um adesivo universal ao esmalte e à dentina - Ilha, Bruna Dias (2021)
In the present study, two papers are presented involving the study of the effect of erosive challenge, as well as the use of anti-erosive dentifrice, on bond strength (μSBS) and on the adhesion stability of a universal adhesive - Scotchbond Universal-(SBU) to enamel and dentin. The first article aimed to investigate the influence of a SnCl2 containing toothpaste on teeth with erosion lesions in the μSBS of the SBU to enamel and dentin. 120 bovine incisors were randomly divided into 12 groups-(n=10) according to: a)substrate: enamel/dentin; b)substrate condition: sound/eroded (immersion in cola based drink)/eroded-treated (immersion in cola based drink-toothpaste application); c)SBU application strategy: etch-and-rinse (ER)/self-etching (SE). Four composite resin cylinders (0.96mm-diameter/1mm-height) were built on each flat buccal surface. 2 cylinders were tested at each evaluation time. For μSBS evaluation, the microshear test was performed immediately after 24 hours and after 6 months of storage (distilled water, 37°C). μSBS-(Mpa) values were analyzed using three-factor ANOVA. In dentin, there was significant cross-interaction among the three factors observed (P=0.023). Eroded dentin reduced μSBS-(24h) in ER. Treatment with anti-erosive toothpaste also reduced μSBS values to dentin, regardless of the strategy used. In enamel, there was no significant interaction between the factors. The isolated factors, substrate condition (P=0.026), application strategy (P=0.004) and storage time (P=0.016) were significant. The eroded enamel had no impact on μSBS, compared to sound enamel. The erosive challenge negatively impacts the μSBS of the SBU, in dentin, used in the ER strategy, while the treatment with anti-erosive toothpaste compromises the adhesion to dentin in both strategies. Both the erosive challenge and the treatment do not impair enamel adhesion. The aim of the second study was to evaluate the effect of the erosive challenge after adhesive and restorative procedures on enamel and dentin, on the μSBS stability of the SBU adhesive applied in the two etching strategies. 80 bovine incisors were randomly assigned into 8 groups-(n=10) according to: a)substrate: enamel/dentin; b)SBU application strategy: ER/SE; c)challenge after restoration: erosive challenge in cola drink/storage in artificial saliva. Four composite resin cylinders were built on each flat surface, 2 of which were submitted to the microshear test to determine the μSBS, immediately after the erosive challenge and storage in artificial saliva for 7 days and 2 after 6 months of storage (distilled water, 37°C). μSBS-(Mpa) values were analyzed using three-factor ANOVA. The isolated factors, challenge after restoration, application strategy and storage time were statistically significant (P=0.000, P=0.048 and P=0.000, respectively). The μSBS values in eroded dentin were reduced in ER strategy. The μSBS stability to dentin was affected in the control group. However, lower immediate μSBS values were found in the eroded group. In enamel, statistical significance was observed for the application strategy isolated factor (P=0.00), the μSBS values in ER were higher than in SE group. The erosive challenge after restorative procedures does not compromise the stability of adhesion to enamel and dentin; however, it impairs the immediate μSBS to the dentin, when the ER strategy is used.